Chronic myelomonocytic leukemia as a transformation from polycythemia vera. (2019) - Andrei, Mirela; Pandey, Anita; Avezbakiyev, Boris; Wang, Jen Chin
Abstract: The hallmark of Polycythemia vera (PV) is the presence of JAK2 V617F mutation and increased RBC mass. Chronic myelomonocytic leukemia (CMML) is defined as persistent blood absolute monocyte count (AMC) >/= 1 × 10 9 /L for at least 3 months with myeloid cell dysplasia. Few cases of evolved CMML from PV have been described. We present a case of PV that progressed to CMML. We demonstrated the CMML clone was most likely derived from PV- JAK2 V617F clone. This clone carried a complex genetic mutations of ASXL1, RUNX1, SRSF2 and TET2, NRAS, KRAS, plus CMML cells were of the classical phenotype CD14 + CD16 − by flow cytometry.